The orchids genus Dilochia in Indonesia - Sulistiarini, Diah (Research Center for Biology, 2012)
Five species of Dilochia (D. cantleyi, D. longilabris, D. parviflora, D. rigida and D. wallichii) have been recognized in Indonesia. One species from Sumatra is proposed as new species. Descriptions and identification key to all species based on morphological characters are presented.